Evaluation and optimization of microbial DNA extraction from fecal samples of wild Antarctic bird species. Issue 1 (1st January 2017) - Eriksson, Per; Mourkas, Evangelos; González-Acuna, Daniel; Olsen, Björn; Ellström, Patrik
ABSTRACT: Introduction : Advances in the development of nucleic acid-based methods have dramatically facilitated studies of host–microbial interactions. Fecal DNA analysis can provide information about the host's microbiota and gastrointestinal pathogen burden. Numerous studies have been conducted in mammals, yet birds are less well studied. Avian fecal DNA extraction has proved challenging, partly due to the mixture of fecal and urinary excretions and the deficiency of optimized protocols. This study presents an evaluation of the performance in avian fecal DNA extraction of six commercial kits from different bird species, focusing on penguins. Material and methods : Six DNA extraction kits were first tested according to the manufacturers' instructions using mallard feces. The kit giving the highest DNA yield was selected for further optimization and evaluation using Antarctic bird feces. Results : Penguin feces constitute a challenging sample type: most of the DNA extraction kits failed to yield acceptable amounts of DNA. The QIAamp cador Pathogen kit (Qiagen) performed the best in the initial investigation. Further optimization of the protocol resulted in good yields of high-quality DNA from seven bird species of different avian orders. Conclusion : This study presents an optimized approach to DNA extraction from challenging avian fecal samples.